Academic buoyancy training to improve school engagement for high school students in Cimahi - Yosi, Alicia; Savitri, Jane; Rohinsa, Meilani (Universitas Ahmad Dahlan, 2024)
High school students are more susceptible to feelings of boredom in their learning due to the increasingly complex academic expectations that arise during adolescence, which can lead to a decrease in school engagement among students. This study aims to determine the impact of academic buoyancy training on enhancing school engagement. The research employed an experimental method utilizing a purposive sampling technique to select a sample of 37 grade XI students from Santa Maria 3 High School in Cimahi City, all of whom exhibited low levels of school engagement. The intervention consisted of academic buoyancy training provided to 18 low-engaged students, while 19 students were assigned to a control group. Following the intervention, school engagement data were analyzed using the SPSS 25.0 software, employing differential test analysis techniques, specifically the Mann-Whitney U and Wilcoxon Rank statistical tests. The results indicated that the academic buoyancy training intervention significantly improved school engagement among high school students. Furthermore, the effect size analysis revealed that the academic buoyancy training intervention had a moderate impact on enhancing school engagement in this population.